Attenuation of streptozotocin induced high fat diet exacerbated dyslipidemia mediated hepatic and aortic injuries in male pigs by camel milk. Issue 1 (31st December 2023) - Rilwan, Hadiza Bello; Adebisi, Sunday Samuel; Timbuak, James Abrak; Oladele, Sunday Blessing; Muhammad, Aliyu; Makena, Wusa; Sadeeq, Adamu Abubakar
ABSTRACT: Dyslipidemia, diabetes, and the upregulation of receptors for oxidized low-density lipoprotein all contribute to hepatic and aortic endothelial dysfunction. The current research examined how camel milk could possibly decrease induced Streptozotocin-high fat diet-aggravated dyslipidemia-mediated damage in male pig hepatic and aortic tissues. Twenty-five pigs were separated into five groups of five pigs each, with five non-atherosclerotic pigs in the control group and twenty atherosclerotic pigs in the experimental groups. Groups 1 and 2 received distilled water as the standard control and atherosclerotic control groups, respectively, while Groups 3 and 4 received camel milk at 250 mL/day and 500 mL/day, respectively, and Group 5 received Metformin at 500 mg/day. The experiment lasted ten weeks. After 10 weeks, all of the pigs were euthanized. The lipid profile and liver enzyme levels were determined from the analysis of blood serum and the histology of the liver and aortic. When pigs administered, camel milk were compared to atherosclerotic control pigs, there was a significant decrease (p 0.05) in cholesterol, triglyceride, low density lipoprotein (LDL), and very low-density lipoprotein (VLDL) levels, while a significant increase in high density lipoprotein levels was observed in pigs that received camel milk. Also, pigs in groups that received camel milk had their liver enzyme parameters (ALP, AST, ALT, GGT, LDH, and CK-MB) significantly lowered when compared with atherosclerotic control pigs. Similarly, treatment with camel milk ameliorates aortic tissues from degradation and reduces histological liver steatosis, and it also decreases the expression of LOX-1 mRNA in the aorta of atherosclerotic pigs.